2013
DOI: 10.1002/pola.26942
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SET–LRP‐induced galactoglucomannan‐diblock copolymers

Abstract: Polysaccharides are biorenewable and biodegradable starting materials for the development of functional materials. The synthesis of a monofunctional macroinitiator for single electron transfer-living radical polymerization was successfully developed from a wood polysaccharide-O-acetyl galactoglucomannan (GGM) using a beforehand synthesized amino-functional a-bromoisobutyryl derivative applying reductive amination. The GGM macroinitiator was employed to initiate a controlled radical polymerization of [2-(methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Flavonoid‐based copolymer brushes with a naringin core and block copolymer side chains composed of amphiphilic PMMA‐ b ‐PNIPAM have been synthesized for the first time using only 40 ppm of Cu catalyst complex, following the se ATRP procedure (Table ). Until now, PMMA‐ b ‐PNIPAM block copolymers were synthesized by ATRP approaches but always with huge amounts of catalyst: 6 300 to 147 400 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flavonoid‐based copolymer brushes with a naringin core and block copolymer side chains composed of amphiphilic PMMA‐ b ‐PNIPAM have been synthesized for the first time using only 40 ppm of Cu catalyst complex, following the se ATRP procedure (Table ). Until now, PMMA‐ b ‐PNIPAM block copolymers were synthesized by ATRP approaches but always with huge amounts of catalyst: 6 300 to 147 400 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, PMMA-b-PNIPAM block copolymers were synthesized by ATRP approaches [79][80][81][82] but always with huge amounts of catalyst:…”
Section: Analysis Of Graft (Co)polymer Brushesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, a monofunctional initiator was successfully synthesized from galactoglucomannan on its reducing end using an amino functional α-bromoisobutyric derivative. 201 The macroinitiator was used to initiate SET-LRP of MMA, MAETC, and NIPAM using Cu(0)/Me 6 -TREN as a catalyst producing diblock copolymers with molar masses ranging from 5,200 to 50,000 g mol −1 . The formed diblock copolymers could be used in food formulations as stabilization agents due to their easily tunable properties such as amphiphilicity or charge.…”
Section: Modification Of Polysaccharides By Set-lrpmentioning
confidence: 99%
“…However, polysaccharide-derivative-blockoligosaccharides (Breitenbach et al 2017;de Medeiros Modolon et al 2012) or polysaccharide-derivative-block-oligopeptides have not received much attention from researchers. Carbohydrate-based block copolymers with polyester (Fajardo et al 2014;Liu and Zhang 2007), poly(methyl methacrylate) (Dax et al 2013;Togashi et al 2014), poly(styrene) (Loos and Müller 2002;Otsuka et al 2013;Yagi et al 2010), poly(N-isopropylacrylamide) (Dax et al 2013;Otsuka et al 2012), poly(γ-benzyl-L-glutamate) (Kamitakahara et al 2014), and poly(3hexylthiophene) (Sakai-Otsuka et al 2017) polyisoprene (Hung et al 2017), and poly(ethyleneoxide) (Akiyoshi et al 1999) have been reported. Shoichet and her colleagues focused on a physical blend of hyaluronan and methylcellulose covalently linked to peptides for tissue-engineering purposes (Parker et al 2016).…”
Section: Introductionmentioning
confidence: 99%